Open museum: between visibility and visuality. Composing nets and views of afection. from fragments to constelations - Amaral, Lilian (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2009)
This paper depicts a transdisciplinary research project focused on contemporary dialogic approach based on art and public sphere. It discusses the role of contemporary museum as a research’s space and artistic conversation based on processual and collaborative experiences at intercultural contexts. It develops procedures inspired on museum practices; and it has urban imaginaries as territories of analyses that configure new archaeologies of contemporary urban memory. From the spectacle to the city’s experience, it traverses through differences between visuality and visibility, the city and the site. It operates a distinction between visuality and visibility, reception and perception, communication and information. Through all those differences, metamorphoses of the look occur.